Climate smart agriculture short courses - Murang'a University of Technology; Alliance of Bioversity International and CIAT (2025)
The Climate Smart Agriculture (CSA) course offered by Murang’a University of Technology (MUT) equips learners with practical knowledge and tools to enhance agricultural resilience to climate change in their different lines of work or profession. Through six modules, the learners explore climate-smart technologies, sustainable resource management, and agrifood system modeling. The program targets extension officers, researchers, farmers, self employed e.g., consultants and policy actors in the agriculture sector and related subsectors. Supported by AICCRA through the Alliance of Bioversity and CIAT, the course promotes sustainable solutions for climate-resilient food systems in Africa.